Asian alternatives for a sustainable world : transborder engagements in knowledge formation - Nippon Foundation. host body; Universiti Kebangsaan Malaysia. Institute of Malaysia and International Studies (IKMAS). Asian Public Intellectuals (API) (Selangor : Universiti Kebangsaan Malaysia, 2009)
PSZJBL